An overview of the success of the “PADAMU DHIVA” program on adherence to consuming ARVs for HIV-AIDS patients at the Balowerti Primary Health Care Center - Twoti Dika Parmanasari; Hanie Kusuma Wardani (Universitas STRADA Indonesia, 2023)
Adherence to anti-retroviral (ARV) treatment in HIV/AIDS patients is essential to suppress the growth of the virus optimally and improve the patient's quality of life. HIV/AIDS patients can only miss 1-2 doses within one month of consuming ARVs, meaning their adherence to ARVs must be more than 95%. A medication assistance program for HIV/AIDS patients on ARV (Padamu Dhiva) was created to achieve and maintain this high adherence. This study aims to provide an overview of the successful implementation of the